2016
DOI: 10.1038/cddis.2016.92
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ/P53 signaling is required for curcumin to induce hepatic stellate cell senescence

Abstract: Activation of quiescent hepatic stellate cells (HSCs) is the major event in hepatic fibrogenesis, along with enhancement of cell proliferation and overproduction of extracellular matrix. Although inhibition of cell proliferation and induction of apoptosis are potential strategies to block the activation of HSCs, a better understanding of the senescence of activated HSCs can provide a new therapeutic strategy for prevention and treatment of liver fibrosis. The antioxidant curcumin, a phytochemical from turmeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 37 publications
(41 reference statements)
5
105
0
1
Order By: Relevance
“…A few studies have recently revealed that cellular senescence can be regulated by nuclear receptors (Graziano, Johnston, Deng, Zhang, & Gonzalo, 2016; Jin et al, 2016; O'Loghlen et al, 2015; Wu et al, 2015; Zambrano et al, 2014; Zhu et al, 2014). Nuclear receptors form a large family, and only a few of them have been implicated so far in cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have recently revealed that cellular senescence can be regulated by nuclear receptors (Graziano, Johnston, Deng, Zhang, & Gonzalo, 2016; Jin et al, 2016; O'Loghlen et al, 2015; Wu et al, 2015; Zambrano et al, 2014; Zhu et al, 2014). Nuclear receptors form a large family, and only a few of them have been implicated so far in cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…PPARg is also reported to be involved in liver fibrosis. During the activation process of HSCs and liver fibrosis, PPARg expression is gradually lowered, whereas it is highly expressed in quiescent HSCs (21,22). Overexpression of PPARg in activated HSCs switches HSCs to a more quiescent phenotype and strengthens adipogenic ability of HSCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin regulates PPARγ coactivator-1α expression by AMPK pathway in HSCs in vitro [217]. Activation of PPARγ/p53 signaling is required for curcumin to induce HSC senescence [218]. Thiazolidinediones (TZDs), synthetic insulin sensitizing PPARγ agonists such as pioglitazone and rosiglitazone, improved steatosis and lobular inflammation but not fibrosis in non-cirrhotic NASH patients in a phase 3 trial (PIVENS trial) [219].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Soluble egg antigens (SEA) of schistosoma japonicum induce senescence of activated HSCs by activating FoxO3a/SKP2/p27 pathway [317]. HSC senescence can also be induced by phytochemicals such as curcumin by activating PPARγ/p53 signaling [218]. RAR/RXR and PPARγ may play a role in inducing HSC senescence as antifibrotic therapy [318].…”
Section: Deactivation and Elimination Of Fibrogenic Hscsmentioning
confidence: 99%